Character Building laws of leadership - Washington, Booker T. (Executive Books, 2007)
Despite superficial and temporary signs which might lead one to entertain a contrary opinion, there was never a time when I felt more hopeful for the race than I do at the present. The great human law that in the end recognizes and rewards merit is everlasting and universal.
Read by Charlie Jones
Keywords: Character Building